Synergy of phosphate recovery from sludge-incinerated ash and coagulant production by desalinated brine. (1st March 2023) - Wang, Xiangyang; Shi, Chen; Hao, Xiaodi; van Loosdrecht, Mark C.M.; Wu, Yuanyuan
Highlights: 88 wt% of P in the used ash was recovered as Ca-P with reasonable heavy metals. Fe 3+ in the ash was extracted and stripped for coagulant production (FeCl3 ). Al 3+ removed from the ash was used for a liquid PAC production with desalinated brine. The PAC behaved almost same in coagulation performance as a commercial PAC. 'Blue' phosphate and 'green' coagulants would promote the circular economy. Abstract: Wet-chemical approach is widely applied for phosphate recovery from incinerated ash of waste activated sludge (WAS), along with metals removed/recovered. The high contents of both aluminum (Al) and iron (Fe) in WAS-incinerated ash should be suitable for producing coagulants with some waste anions like Cl − and SO4 2− With acid (HCl) leaching and metals' removing, approximately 88 wt% of phosphorus (P) in the ash could be recovered as hydroxylapatite (HAP: Ca5 (PO4 )3 OH); Fe 3+ in the acidic leachate could be selectively removed/recovered by extraction with an organic solvent of tributyl phosphate (TBP), and thus a FeCl3 -based coagulant could be synthesized by stripping the raffinate with the original brine (containing abundant Cl − and SO4 2− ). Furthermore, a liquid poly-aluminum chloride (PAC)-based coagulant could also be synthesized with Al 3+ removed from the ash and the brine, which behaved almost the same in the coagulation performance as a commercial coagulant on both phosphate and turbidity removals. Both P-recovery from the ash and coagulant production associated with the brine would enlarge the markets of both 'blue' phosphate and 'green' coagulants.